2021
DOI: 10.3390/polysaccharides2040045
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chitosan Films from Edible Crickets and Their Performance as a Bio-Based Food Packaging Material

Abstract: Edible insects have gained attention due to their impressive nutritional composition, as well as their efficient use of natural resources. However, a research gap remains on the applications of insect chitosan, especially as it relates to their potential use as food packaging material. Chitosan from two reared cricket species (Acheta domesticus and Gryllodes sigillatus) was evaluated for use as food packaging material. Cricket chitosan films (CCF) were structurally similar to commercial shrimp chitosan films (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This assumption does not apply to edible films that are hydrophilic. The maximum permeability value of the NCHR membrane film in this investigation, which was affected by a 0.9% NaCl solution, indicates that this solution will increase the complexity of the water transport mechanism to and from the hydrophilic chitosan film [85]. The nonlinear water absorption isotherm and the water content-dependent diffusion isotherm contribute to this complexity [86].…”
Section: Table 5 Wvtr Assessment Of Film Membrane Of Nchr Influenced ...mentioning
confidence: 75%
“…This assumption does not apply to edible films that are hydrophilic. The maximum permeability value of the NCHR membrane film in this investigation, which was affected by a 0.9% NaCl solution, indicates that this solution will increase the complexity of the water transport mechanism to and from the hydrophilic chitosan film [85]. The nonlinear water absorption isotherm and the water content-dependent diffusion isotherm contribute to this complexity [86].…”
Section: Table 5 Wvtr Assessment Of Film Membrane Of Nchr Influenced ...mentioning
confidence: 75%
“…Priyadarshi et al reported the formation of the homogeneous film with chitosan, whereas the glycerol-added films were inhomogeneous in texture and bulges containing glycerol. Malm et al observed homogeneous, smooth films which were free of cracks and pores. Rodrigues et al reported pure chitosan film has a smooth surface with small clusters, probably agglomerates of chitosan molecules, and with the addition of nanocomposites, clay nanoparticle agglomerates were observed.…”
Section: Resultsmentioning
confidence: 99%
“…All these results are similar to the reported data on chitosan. 44,48,57,62 Further, Malm et al 57 reported that chitosan extracted from shrimp is more transparent than the one extracted from crickets. We found that glycerol-added films showed an increase in the transmittance in all regimes, including the transparency in the visible regime.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Biodegradable films and edible chitosan coatings have emerged as sustainable alternatives to compete with conventional non-biodegradable food packaging technologies. The development of chitosan-based films from edible cricket species and their application in the food industry was investigated by Malm and coworkers [103]. Zehra et al prepared a chitosan-based film with thyme essential oil, zinc oxide (ZnO), polyethylene glycol (PEG), nanoclay (NC), and calcium chloride (CaCl 2 ) as additives [104].…”
Section: Chitosanmentioning
confidence: 99%